2007
DOI: 10.1021/ef070071k
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Effects of Charge Stratification on Combustion and Emissions

Abstract: A fully coupled multidimensional computational fluid mechanics and reduced chemical kinetics model is adopted to investigate the effects of charge stratification on combustion and emissions. Seven different kinds of imposed stratification have been introduced according to the position of the maximal local fuel/air equivalence ratio in the cylinder at intake valve close. The results show that the charge stratification results in stratification of the in-cylinder temperature. The former four kinds of stratificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Both experimental and numerical studies have been conducted to explore the charge stratification to control the HCCI combustion by port injection and DI of the same n-heptane fuel Zheng and Yao, 2007). The stratification can be altered by changing the ratio between the port and DI fuel mass and also the DI timing.…”
Section: Charge Reactivity and Stratification Controlled Combustion Smentioning
confidence: 99%
“…Both experimental and numerical studies have been conducted to explore the charge stratification to control the HCCI combustion by port injection and DI of the same n-heptane fuel Zheng and Yao, 2007). The stratification can be altered by changing the ratio between the port and DI fuel mass and also the DI timing.…”
Section: Charge Reactivity and Stratification Controlled Combustion Smentioning
confidence: 99%
“…Unfortunately, the coupling process incurs a high computational cost, rendering this method unattractive to researchers. As an alternative, many researchers have adopted reduced chemical kinetics coupled with CFD. Noel et al used reduced chemical kinetics of n -heptane with multidimensional CFD code to simulate HCCI combustion in diesel engines. Their study shows that the reduced mechanism behaves similarly to the detailed models for the description of the two-stage phenomenon and also for the temperature and pressure inside the cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…Kim and Lee used KIVA-3V/reduced chemical kinetics to study the effects of injection strategy on the combustion process and the chemical reaction path in an HSDI diesel engine. Zheng and Yao adopted a fully coupled multidimensional CFD and reduced chemical kinetics model to investigate the effects of charge stratification on HCCI combustion and emissions. Mo et al used a DME reduced chemical kinetics model coupled with CFD to predict combustion and emissions of DME HCCI.…”
Section: Introductionmentioning
confidence: 99%
“…A little inhomogeneity in fuel concentration and temperature in mixing can produce significant effects on autoignition and combustion processes. Utilizing the inhomogeneity (charge stratification) is an important path to achieve clean and high-efficiency combustion in engines. It can be concluded that stratification combustion has the potential to extend the high-load limits for HCCI operation and reducing UHC and CO emissions.…”
Section: Introductionmentioning
confidence: 99%